Evaluation of referral documentation in pediatrics emergency transfers: A cross-sectional observational study - Nitika Agrawal; Rakesh Kumar; Savita Pandey; Alpa Gupta; Kunal Das; Ashish Simalti (Journal of Pediatric Critical Care)
Background: Inadequate handover documentation may result in delay and adverse outcomes during continuity of care. This is much more important in interfacility transfers where improper or missing documentation of prior events from a referring point may result in a break in the continuity of care. Subjects and Methods: This was a cross-sectional observational study done to evaluate the quality of referral documentation available with the patients who were referred to a tertiary care center after consultation in a peripheral center between March 2024 and May 2024. A semi-structured pro forma was used to collect transfer characteristics and quality of transfer documents at the time of admission. Results: A total of 156 children were enrolled in the study. The mean age of children was 6.81 ± 5.79 years. 68 (43.6%) were referred from a private nursing home. Healthcare workers accompanied only 19 (12.2%) children. Referral documentation was available in 121 (77.6%). 96/121 (61.5%) had handwritten referral papers. Pretransport communication was received only in one patient. Patients being referred by private physicians (70.8%) and smaller hospitals (80.9%) have better documentation than medical colleges (40.9%) (P = 0.03), patients being transported in an ambulance (87.23% vs. 73.4%, P = 0.05) have higher chances of having referral documentation. Conclusions: There is a lack of pretransfer referral communication and quality referral documents. Pediatric referral services in the region are fragmented and nonuniform. There is a need to improve pediatric referral documentation and transfer services.